Application of Saw Dust Ash as Partial Replacement for Cement in the Production of Interlocking Paving Stones - Raheem, Akeem Ayinde; Adedokun, Solomon Idowu; Raphael, Ajayi Babatunde; Adedapo, Adedoyin Olakunle; Olayemi, Adegboyega Biliki (International Journal of Sustainable Construction Engineering and Technology, 2017)
As a way of reusing and converting industrial by-products into useful materials for the construction industry, this paper investigated the application of Saw dust ash (SDA) as partial substitute for ordinary Portland cement (OPC) in the production of interlocking paving stones. The study examined the oxide composition of SDA to determine its suitability as a pozzolanic material. Some characteristics of paving stones with SDA as a substitute for OPC were investigated and the results indicated that SDA is a good pozzolan having satisfied the required standards. The compressive strength of the samples, with substitution levels ranging from 5 to 25% cured for 3â€“56 days, was lower at initial curing period but improved significantly at later days. 5% substitution level showed an increase in strength compared to 0% SDA paving stones regardless of curing period.Â  Density decreased with increasing ash content, whereas water absorption increased with SDA content. The study therefore indicated that SDA paving stones can gain higher strength than the conventional ones at longer curing periods, which is as a result of its pozzolanic reactions.